2008
DOI: 10.1590/s0102-76382008000300009
|View full text |Cite
|
Sign up to set email alerts
|

Aplicabilidade do escore de risco de Ambler para pacientes com substituição valvar por bioprótese de pericárdio bovino

Abstract: odds-ratio (OR).Results: The mortality rate was 14.3%, which was higher than the estimated mortality rate (3%, according to Ambler's mean score of 6, (p<0.01)). Patients who died presented a mean score of 8.26, which was higher than the survivors' average score of 5.68. Characteristics of increased risk were emergency surgery (OR=10.87), dialysis (OR=6.10), and age higher than 80 years (OR=6.10). Our sample indicates an area under the ROC curve of 72.9% (accepted value > 70%). Conclusion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…The surgical variables assessed were associated surgery (CABG and tricuspid valve surgery), valve surgery reoperation and type of surgery (elective or urgent). These characteristics are similar to the study by Ambler et al [2] and were previously used by the authors of this study in studies with valve bioprostheses [10].…”
Section: Outcomes and Definition Of Risk Factorssupporting
confidence: 85%
See 1 more Smart Citation
“…The surgical variables assessed were associated surgery (CABG and tricuspid valve surgery), valve surgery reoperation and type of surgery (elective or urgent). These characteristics are similar to the study by Ambler et al [2] and were previously used by the authors of this study in studies with valve bioprostheses [10].…”
Section: Outcomes and Definition Of Risk Factorssupporting
confidence: 85%
“…In a study performed in this institution [10], with patients who had undergone implant of bioprosthesis, increased odds ratio was observed for associated tricuspid surgery (OR 3.71), combined mitral and aortic surgery (OR 2.86) and females (OR 2.43). Other characteristics with higher OR, such as emergency surgery, dialysis, age over 80 years and two or more previous surgeries were not highlighted in this study.…”
Section: Discussionmentioning
confidence: 93%
“…In Brazil, Brandao et al 30 , in a study of double-leaflet mechanical prosthesis implant, reported a mitral mortality of 13.5% and an aortic mortality of 7.5%. De Bacco et al 15 , also in our country, in a retrospective study of 703 patients that were submitted to surgery for the implant of bovine pericardial bioprosthesis, reported a mortality rate of 14.3% of in-hospital deaths and 12.1% when the surgery was elective. What literature demonstrates, therefore, is a broad oscillation in the mortality rate, which stimulates the search for factors that can contribute to in-hospital mortality.…”
mentioning
confidence: 79%
“…This attitude is justified by the ready availability of medical information considered as part of the hospital record, and also because they had been previously used by the authors [13][14][15]. We opted to include pulmonary arterial hypertension as an additional factor, but other recognized factors were excluded, such as chronic obstructive pulmonary disease and peripheral vascular disease [3], which were not always correctly referred or quantified in hospital records.…”
Section: Fig 1-risk Factors For Hospital Mortality With Expression mentioning
confidence: 99%
“…The porcine bioprostheses are used in approximately 40% of patients who underwent implantation of biological valve replacements, however, the results of these procedures have not been evaluated, unlike what happened with the surgical valve replacement with a bovine pericardial prostheses [13,14] and mechanical prostheses [15], whose analysis has allowed to stratify the implant surgical risk and decrease the operative mortality.…”
Section: Introductionmentioning
confidence: 99%